Identification of new families and variants in autosomal dominant macular dystrophy associated with THRB - Lidia Fernández-Caballero; Fiona Blanco-Kelly; Saoud Tahsin Swafiri; María Inmaculada Martín-Mérida; Mathieu Quinodoz; Mukhtar Ullah; Ester Carreño; María Pilar Martin-Gutierrez; Blanca García-Sandoval; Pablo Minguez; Carlo Rivolta; Marta Corton; et al. (Scientific Reports)
Abstract THRB encodes thyroid hormone receptor β which produces two human isoforms (TRβ1 and TRβ2) by alternative splicing. The first THRB variant associated with autosomal dominant macular dystrophy (ADMD), NM_001354712.2:c.283 + 1G > A, was recently described. This study aims to refine the ophthalmologic phenotype, report a novel THRB variant, and investigate the impact of these splicing variants at the protein level. THRB variants were identified by re-analysis of next-generation sequencing data from the FJD database. Family segregation was performed using Sanger sequencing. Clinical data were collected from self-reported ophthalmic history questionnaires and ophthalmic exams. Functional splicing test was performed by in vitro minigene approach. We identified 12 patients with ADMD from 3 families carrying variants in THRB. Two families carried the variant NM_001354712.2:c.283 + 1G > A, and one the novel variant NM_001354712.2:c.283G > A. Patients exhibited common ophthalmologic findings with disruption of subfoveal ellipsoid layers, and variable onset of symptoms. Splicing assays showed complete exon 5 skipping or a 6 bp deletion in both variants. Our results support the association of THRB with ADMD. The high intra-familial variability could be influenced by phenotype modifiers. Aberrant TRβ1/TRβ2 proteins could lead to a gain-of-function mechanism. Including THRB in inherited retinal dystrophy genetic panels could enhance diagnoses and clinical patient management.